2016
DOI: 10.1097/phm.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Whole-Body Vibration Combined with Task-Related Training on Upper Extremity Function, Spasticity, and Grip Strength in Subjects with Poststroke Hemiplegia

Abstract: The findings indicate that the use of whole-body vibration training combined with task-related training has more benefits on the improvement of arm function, spasticity, and maximal grip strength than conventional upper limb training alone or with whole-body vibration in people with poststroke hemiplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…Recent studies [ 9 , 10 , 17 19 ] also found remarkable benefits of vibration on poststroke spasticity and gait performance though the rest of the vibration studies did not [ 2 , 20 22 ]. Lukashevich and Likhachev [ 17 ] studied focal vibration for its ability to reduce poststroke spasticity in 13 volunteers and found that 80 hz and 0.3 amplitude focal vibrations on gastrocnemius muscle reduce maximum amplitudes of H-reflex and M-response as the reflectors of calf muscle spasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [ 9 , 10 , 17 19 ] also found remarkable benefits of vibration on poststroke spasticity and gait performance though the rest of the vibration studies did not [ 2 , 20 22 ]. Lukashevich and Likhachev [ 17 ] studied focal vibration for its ability to reduce poststroke spasticity in 13 volunteers and found that 80 hz and 0.3 amplitude focal vibrations on gastrocnemius muscle reduce maximum amplitudes of H-reflex and M-response as the reflectors of calf muscle spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group had more benefits after 4 weeks of training on the mentioned issues than the control group and the WBV group alone also in accordance with our study. Lee et al [ 19 ] found also short-term (after 30 minutes) improvement in Ashworth scores, F-wave, and motor function of the hand in poststroke patients after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…18,21 Several studies have pointed to the significant effects of mechanical vibration in many clinical conditions, such as hemiplegia, spinal cord injury, cerebral palsy, and osteoporosis. [22][23][24][25] Given the known effects of WBVE on peripheral muscle function, functional independence, and all considerations, it is possible to suggest that WBVE seems to be an important Jussara R. Chaves e cols. • WBVE In heart surgery postoperative modality of exercise for the management of individuals with physiological changes related to decreased quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The development and refinement of upper limb rehabilitation strategies after a stroke has the potential to improve an individual's function as well as decrease the burden on caregivers and the health care system (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%